P195 Case Series: How Useful Are Fleischner Guidelines For Nodule Surveillance in a District General Hospital?. (19th November 2012) - Lee, RW; Millward, KE; Ossai, FE; Ellis, D; Townsend, M
Abstract : Background: Surveillance of pulmonary nodules aims to identify early-stage lung cancers where radical therapy can offer cure. Interval CT scans track nodule characteristics with Fleischner criteria commonly used in an attempt to standardise care. There remains debate regarding the applicability of Fleischner guidance in populations of UK patients that can differ substantially from those included in existing studies that define the Fleischner recommendations. Objectives: Audit compliance of pulmonary nodule follow up with Fleischner Guidelines. Compare local outcomes with those used to create Fleischner guidelines. Compare local compliance with published compliance. Methods: Patients referred to a specialist respiratory nurse service for pulmonary nodule surveillance since 2008 (including patients already under surveillance) with opportunity for 2 years of completed follow-up were included with retrospective review of the nodule database/electronic records and imaging. Patients were risk stratified according to nodule size and Fleischner risk category (e.g. smoking). Results: 111 patients under surveillance were identified of whom 56 were Male and 55 Female with median age 67 (34–91) years. 67 were solitary and 44 were multiple. Patients were stratified to Low- and High-risk groups according to main nodule size: (L1–4 or H1–4 respectively). Each group included; High-risk: H1 (<=4mm)10, H2 (>4–6mm) 25, H3 (>6–8mm) 19 and H4 (>8mm) 36 cases and Low-risk: L1 (<=4mm) 0, L2 (>4–6mm) 5, L3 (>6–8mm) 4 and L4 (>8mm) 3 cases. 89 patients completed standard follow-up and were discharged. Positive scans included Lung tumours (3) - (two underwent lobectomy); Aspergilloma (1); Rectal carcinoma (1)- discovered by non-Fleischner abdominal CT. Surveillance was discontinued for: Patient choice/co-morbidity (8); Nodule resolution (3); Not documented/lost (6). Conclusion: Fleischner guidelines were well adhered to and were also utilised where their application is less well defined e.g. development of a new nodule during follow-up prompted either re-initiation or more commonly continued/modified trajectory of Fleischner - an area notably not well covered in current guidance. Furthermore principals of Fleischner recommendations were applied to multiple nodules but management of such patients is often not as easily followed as solitary nodules. MacMahon et al, University of Chicago, Radiology 2005; 237:295–400.